S94 Stereotactic Radiotherapy for Stage 1 Non Small Cell Lung Cancer: How much occult nodal disease are we missing?. (19th November 2012) - Robson, JM; Vaidyanathan, S; Callister, MEJ
Abstract : Introduction and Objectives: Stereotactic Ablative Body Radiotherapy (SABR) has been developed over the last two decades as a method of treating peripheral early stage (T1, T2) NSCLC. It is considered as a valid option for treatment when surgery is high risk or declined. Many clinicians now question whether SABR can be considered as a genuine alternative to surgery for peripheral stage I NSCLC. One concern about any comparison with surgery is that those patients who receive SABR may miss out on adjuvant chemotherapy due to lack of pathological nodal staging that would be done post operatively. Our aim was to determine what proportion of cases this might represent. Methods: We carried out a retrospective review of surgical resections for lung cancer between 2008 and 2011 at a teaching hospital in Yorkshire. We identified those patients who were staged preoperatively as T1 or T2 with no nodal or distant metastases. We also identified a subgroup of patients with peripheral tumours no greater than 5cm in diameter (i.e. those potentially suitable for SABR). We recorded post operative staging and whether they received adjuvant chemotherapy. Results: We identified 162 cases in total (81 female) of which 13.7% had nodal involvement on post operative staging. Of these, 72.7% received adjuvant chemotherapy. Within the subgroup with peripheral tumours <5cm there were 116 cases of which 7.0% had nodal involvement. Of these, 62.5% received adjuvant chemotherapy. Conclusions: Our findings show that a significant number of patients who are preoperatively staged as N0 do have hilar and/or mediastinal nodal involvement at the time of surgery. However, many of these patients have central tumours not suitable for SABR. In the subgroup of patients with small peripheral tumours, that would potentially be suitable for SABR, this proportion is smaller. It is thought that on direct comparison with surgery those who receive SABR might be more likely to develop recurrent disease due to nodal involvement outside of the radiotherapy field in some patients. Our results suggest that this proportion is small. Any effect on overall survival would be weighed against peri-operative morbidity and mortality.